2019
DOI: 10.3389/fendo.2019.00388
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic Ovary Syndrome and NC-CAH: Distinct Characteristics and Common Findings. A Systematic Review

Abstract: Background: Twenty-one-hydroxylase–deficient non-classic adrenal hyperplasia (NC-CAH) is a very common autosomal recessive syndrome with prevalence between 1:1,000 and 1:2,000 individuals and the frequency varies according to ethnicity. On the other hand, polycystic ovary syndrome has a familial basis and it is inherited under a complex hereditary trait. This syndrome affects 6 to 10% of women in reproductive age and it is the most common endocrine disorder in young women. Our aim was to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 96 publications
0
25
0
Order By: Relevance
“…In our study, in the persistent acne group, increased levels of 17‐OHP beyond 2 ng/ml were seen in eight patients thus by using the cut‐off values suggested by previous authors, only 15.38% of persistent acne patients can be been labeled as NCCAH (Table ). While an ACTH stimulation test could not be performed because of lack of ethical clearance, it must be noted that the cardinal test for confirmation of diagnosis of NCCAH is molecular genetic analysis of the CYP21A2 gene, a facility that we do not have at our center. Also it is pertinent to point out that a diagnosis of NCCAH generally will not change the best choice of treatment, because glucocorticoids are less effective than estrogen‐progestin contraceptives and/or antiandrogens for the treatment of chronic anovulation and hirsutism in women with NCCAH, both of which are notably also used for the treatment of adult female acne without NCCAH as well …”
Section: Discussionmentioning
confidence: 99%
“…In our study, in the persistent acne group, increased levels of 17‐OHP beyond 2 ng/ml were seen in eight patients thus by using the cut‐off values suggested by previous authors, only 15.38% of persistent acne patients can be been labeled as NCCAH (Table ). While an ACTH stimulation test could not be performed because of lack of ethical clearance, it must be noted that the cardinal test for confirmation of diagnosis of NCCAH is molecular genetic analysis of the CYP21A2 gene, a facility that we do not have at our center. Also it is pertinent to point out that a diagnosis of NCCAH generally will not change the best choice of treatment, because glucocorticoids are less effective than estrogen‐progestin contraceptives and/or antiandrogens for the treatment of chronic anovulation and hirsutism in women with NCCAH, both of which are notably also used for the treatment of adult female acne without NCCAH as well …”
Section: Discussionmentioning
confidence: 99%
“…There are no detailed data on fertility issues in patients with P30L mutation except the report of two female patients with P30L mutation and SV phenotype requiring genital surgery and several artificial assisted reproduction cycles [ 40 ]. In populations with a high prevalence of NC CAH, many females are diagnosed as PCOS [ 149 151 ]. NC CAH needs to be excluded before diagnosing PCOS [ 22 , 82 , 152 , 153 ].…”
Section: Somatic Outcomesmentioning
confidence: 99%
“…39 Similarly, in present study, the However, according to their logistic regression study using forward stepping models, it was found that their large steroid panel was no According to the current PCOS diagnosis guideline, 38 it is required and necessary to exclude the possibility of NCAH mimicking the symptoms of PCOS. In a recent review article comparing PCOS and NCAH, 41 on average, 87% of NCAH patients and 25% of PCOS patients showed elevated serum 17-OHP levels, which was the only recommended screening assay to differentiate the two distinct diseases requiring different therapeutic treatments. By contrast, the common androgens such as T and DHEAS were also elevated in NCAH, limiting their applications in differentiating NCAH from PCOS.…”
Section: F I G U R Ementioning
confidence: 99%